PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH, DAN DANA PERIMBANGAN TERHADAP BELANJA MODAL DI KABUPATEN DAN KOTA PROVINSI JAWA TENGAH TAHUN 2018-2021 - Bianca Jaynet Ramadhani; Suprihati Suprihati; LMS Kristiyanti (JURNAL WIRANOMIKA, 2023)
Each region has the authority to manage regional autonomy, PAD is one of the most important revenues for a region. The main source of local revenue comes from regional taxes and regional levies. The purpose of this study was to examine the effect of local taxes, regional levies, and balancing funds on capital expenditures.This study uses data on the realization of the local government budget (APBD) for 2018 to 2021 taken from the Ministry of Finance's Directorate General of Fiscal Balance (DJPK) website. The population in this study are all regencies and cities in Central Java. The sampling technique used was Saturated Sample with a total sample of 35 regions consisting of 29 districts and 6 city. This type of research is quantitative research using descriptive statistical tests, classical assumption tests, determination tests (R2), statistical tests f tests and t tests tested using SPSS version 26. The results of this study indicate that: 1) local taxes affect capital expenditure; 2) regional levies have an effect on capital expenditures; 3) balancing funds have an effect on capital expenditures. With an R square value of 53,8%.Keywords: Regional Taxes, Regional Levies, Balancing Funds, Capital Expenditures.